Bidirectional biomimetic flow sensing with antiparallel and curved artificial hair sensors - Abels, Claudio; Qualtieri, Antonio; Lober, Toni; Mariotti, Alessandro; Chambers, Lily D.; De Vittorio, Massimo; Megill, William M.; Rizzi, Francesco (Beilstein Journal of Nanotechnology, 2019)
Background: Flow stimuli in the natural world are varied and contain a wide variety of directional information. Nature has developed morphological polarity and bidirectional arrangements for flow sensing to filter the incoming stimuli. Inspired by the neuromasts found in the lateral line of fish, we present a novel flow sensor design based on two curved cantilevers with bending orientation antiparallel to each other. Antiparallel cantilever pairs were designed, fabricated and compared to a single cantilever based hair sensor in terms of sensitivity to temperature changes and their response to changes in relative air flow direction.Results: In bidirectional air flow, antiparallel cantilever pairs exhibit an axially symmetrical sensitivity between 40 μV/(m s−1) for the lower air flow velocity range (between ±10–20 m s−1) and 80 μV/(m s−1) for a higher air flow velocity range (between ±20–32 m s−1). The antiparallel cantilever design improves directional sensitivity and provides a sinusoidal response to flow angle. In forward flow, the single sensor reaches its saturation limitation, flattening at 67% of the ideal sinusoidal curve which is earlier than the antiparallel cantilevers at 75%. The antiparallel artificial hair sensor better compensates for temperature changes than the single sensor.Conclusion: This work demonstrated the successive improvement of the bidirectional sensitivity, that is, improved temperature compensation, decreased noise generation and symmetrical response behaviour. In the antiparallel configuration, one of the two cantilevers always extends out into the free stream flow, remaining sensitive to directional flow and preserving a sensitivity to further flow stimuli.
Keywords: artificial hair sensor; biomimetics; flow direction; flow sensing; robotics

(untitled) - Flock, Å.; Wersäll, J. (J. Cell Biol., 1962)

(untitled) - Arkett, S. A.; Mackie, G. O.; Meech, R. W. (J. Exp. Biol., 1988)

Insect Mechanics and Control - Humphrey, J. A.; Barth, F. G. (Medium Flow-Sensing Hairs: Biomechanics and Models, 2007)

Flow Sensing in Air and Water: Behavioral, Neural and Engineering Principles of Operation - Barth, F. G. (The Slightest Whiff of Air: Airflow Sensing in Arthropods, 2014)

(untitled) - Landolfa, M. A.; Miller, J. P. (J. Comp. Physiol., A, 1995)

(untitled) - Jacobs, G. A.; Miller, J. P.; Aldworth, Z. (J. Exp. Biol., 2008)

(untitled) - Kant, R.; Humphrey, J. A. C. (J. R. Soc., Interface, 2009)

(untitled) - Miller, J. P.; Krueger, S.; Heys, J. J.; Gedeon, T. (PLoS One, 2011)

(untitled) - Hudspeth, A. J. (C. R. Biol., 2005)

The Mechanosensory Lateral Line: Neurobiology and Evolution - Denton, E. J.; Gray, J. A. B. (Some Observations on the Forces Acting on Neuromasts in Fish Lateral Line Canals, 1989)

(untitled) - McHenry, M. J.; Strother, J. A.; van Netten, S. M. (J. Comp. Physiol., A, 2008)

The Lateral Line System - van Netten, S. M.; McHenry, M. J. (The Biophysics of the Fish Lateral Line, 2013)

(untitled) - Bleckmann, H.; Mogdans, J.; Engelmann, J.; Kröther, S.; Hanke, W. (Biol. Unserer Zeit, 2004)

The Lateral Line System - Chagnaud, B. P.; Coombs, S. (Information Encoding and Processing by the Peripheral Lateral Line System, 2013)

(untitled) - Hudspeth, A. J.; Corey, D. P. (Proc. Natl. Acad. Sci. U. S. A., 1977)

Progress in Zoology - Bleckmann, H. (Perception of hydrodynamic stimuli in aquatic and semiaquatic animals, 1994)

(untitled) - Chagnaud, B. P.; Bleckmann, H.; Hofmann, M. H. (J. Comp. Physiol., A, 2007)

Boundary-Layer Theory - Schlichtling, H. (Springer, 1979)

(untitled) - Mat Nawi, M. N.; Manaf, A. A.; Arshad, M. R.; Sidek, O. (Microsyst. Technol., 2011)

(untitled) - Tao, J.; Yu, X. B. (Smart Mater. Struct., 2012)

(untitled) - Rizzi, F.; Qualtieri, A.; Dattoma, T.; Epifani, G.; De Vittorio, M. (Microelectron. Eng., 2015)

(untitled) - Shizhe, T. (Microsyst. Technol., 2014)

(untitled) - Liu, G.; Wang, A.; Wang, X.; Liu, P. (Appl. Bionics Biomech., 2016)

(untitled) - Han, Z.; Liu, L.; Wang, K.; Song, H.; Chen, D.; Wang, Z.; Niu, S.; Zhang, J.; Ren, L. (J. Bionic Eng., 2018)

Hot-Wire Anemometry: Principles and Signal Analysis - Bruun, H. H. (Oxford University Press, 1995)

(untitled) - Kälvesten, E.; Vieider, C.; Löfdahl, L.; Stemme, G. (Sens. Actuators, A, 1996)

(untitled) - Svedin, N.; Kalvesten, E.; Stemme, E.; Stemme, G. (J. Microelectromech. Syst., 1998)

(untitled) - Zou, J.; Chen, J.; Liu, C.; Schutt-Aine, J. E. (J. Microelectromech. Syst., 2001)

(untitled) - Klein, A.; Bleckmann, H. (Beilstein J. Nanotechnol., 2011)

(untitled) - Wolf, B. J.; Morton, J. A. S.; MacPherson, W. N.; van Netten, S. M. (Bioinspiration Biomimetics, 2018)

(untitled) - Kuo, J. T. W.; Yu, L.; Meng, E. (Micromachines, 2012)

(untitled) - Chen, J.; Liu, C. (J. Microelectromech. Syst., 2003)

(untitled) - Dijkstra, M.; van Baar, J. J.; Wiegerink, R. J.; Lammerink, T. S. J.; de Boer, J. H.; Krijnen, G. J. M. (J. Micromech. Microeng., 2005)

(untitled) - Krijnen, G. J. M.; Dijkstra, M.; van Baar, J. J.; Shankar, S. S.; Kuipers, W. J.; de Boer, R. J. H.; Altpeter, D.; Lammerink, T. S. J.; Wiegerink, R. (Nanotechnology, 2006)

2009 IEEE 22nd International Conference on Micro Electro Mechanical Systems - Bruinink, C. M.; Jaganatharaja, R. K.; de Boer, M. J.; Berenschot, E.; Kolster, M. L.; Lammerink, T. S. J.; Wiegerink, R. J.; Krijnen, G. J. M. (Advancements in Technology and Design of Biomimetic Flow-Sensor Arrays, 2009)

(untitled) - Izadi, N.; de Boer, M. J.; Berenschot, J. W.; Krijnen, G. J. M. (J. Micromech. Microeng., 2010)

(untitled) - Abels, C.; Mastronardi, V. M.; Guido, F.; Dattoma, T.; Qualtieri, A.; Megill, W. M.; De Vittorio, M.; Rizzi, F. (Sensors, 2017)

(untitled) - Wang, Y.-H.; Lee, C.-Y.; Chiang, C.-M. (Sensors, 2007)

2008 Symposium on Design, Test, Integration and Packaging of MEMS/MOEMS - Wang, Y.-H.; Hsueh, T.-H.; Ma, R.-H.; Lee, C.-Y.; Fu, L.-M.; Chou, P.-C.; Tsai, C.-H. (A microcantilever-based gas flow sensor for flow rate and direction detection, 2008)

2009 4th IEEE International Conference on Nano/Micro Engineered and Molecular Systems - Du, L.; Zhao, Z.; Pang, C.; Fang, Z.; Liu, Y.; Han, Y. (Micro solid state silicon plate wind velocity sensor, 2009)

(untitled) - Du, L.; Zhao, Z.; Pang, C.; Fang, Z. (Sens. Actuators, A, 2009)

(untitled) - Zhou, Y.; Wang, Z.; Wang, C.; Ruan, W.; Liu, L. (J. Micromech. Microeng., 2009)

(untitled) - Zhang, Q.; Ruan, W.; Wang, H.; Zhou, Y.; Wang, Z.; Liu, L. (Sens. Actuators, A, 2010)

(untitled) - Qualtieri, A.; Rizzi, F.; Todaro, M. T.; Passaseo, A.; Cingolani, R.; De Vittorio, M. (Microelectron. Eng., 2011)

(untitled) - Qualtieri, A.; Rizzi, F.; Epifani, G.; Ernits, A.; Kruusmaa, M.; De Vittorio, M. (Microelectron. Eng., 2012)

(untitled) - Rizzi, F.; Qualtieri, A.; Chambers, L. D.; Megill, W. M.; De Vittorio, M. (Soft Matter, 2013)

(untitled) - Abels, C.; Qualtieri, A.; De Vittorio, M.; Megill, W. M.; Rizzi, F. (Bioinspiration Biomimetics, 2016)

(untitled) - Bainbridge, R. (J. Exp. Biol., 1958)

(untitled) - Chen, N.; Tucker, C.; Engel, J. M.; Yang, Y.; Pandya, S.; Liu, C. (J. Microelectromech. Syst., 2007)

Proceedings IEEE Thirteenth Annual International Conference on Micro Electro Mechanical Systems (Cat. No.00CH36308) - Ozaki, Y.; Ohyama, T.; Yasuda, T.; Shimoyama, I. (An air flow sensor modeled on wind receptor hairs of insects, 2000)

(untitled) - Heinrich, M.; Friebe, C.; Schwarze, R. (Proc. Inst. Mech. Eng., Part A, 2016)